Dissecting the mechanisms of environment sensitivity of smart probes for quantitative assessment of membrane properties - Ragaller, Franziska; Andronico, Luca; Sykora, Jan; Kulig, Waldemar; Róg, Tomasz; Urem, Yagmur Balim; Abhinav, Abhinav; Danylchuk, Dmytro I.; Hof, Martin; Klymchenko, Andrey S.; Amaro, Mariana; Vattulainen, Ilpo; et al. (Karolinska Institutet, 2022)
General Description

It contains data sets from Ragaller et al, Open Biology, 2022 (https://doi.org/10.1098/rsob.220175).

It contains Generalized Polarization (GP) values, GP profiles, GP maps, raw spectral images, MD Simulation snapshots, tilt angle distributions, partial density profiles, relaxation time and stokes shift

Abstract



The plasma membrane serves as a crucial platform for a multitude of cellular processes. Its collective biophysical properties are largely determined by the structural diversity of the different lipid species it accommodates. Therefore, a detailed investigation of biophysical properties of the plasma membrane is of utmost importance for a comprehensive understanding of biological processes occurring therein. During the past two decades several environment-sensitive probes have been popular tools to investigate membrane properties. Although these probes are assumed to report on membrane order in similar ways, their individual mechanisms remain to be elucidated. In this study, using model membrane systems, we studied the probes Pro12A, NR12S and NR12A in depth and examined their sensitivity to parameters with potential biological implications, such as the degree of lipid saturation, double bond position and configuration, phospholipid headgroup and cholesterol content. Applying spectral imaging together with atomistic molecular dynamics simulations and time-dependent fluorescent shift analyses, we unravelled individual sensitivities of these probes to different biophysical properties, their distinct localizations and specific relaxation processes in membranes. Overall, Pro12A, NR12S and NR12A serve together as a toolbox with a wide range of applications allowing to select the most appropriate probe for each specific research question.

Data usage

Researchers  are welcome to use the data contained in the dataset for any projects.  Please cite this item upon use or when published. We  encourage reuse using the same CC BY 4.0 License.

Data Content

Excel files for graphs

Microscopy Images

Software to open files

.csv - Microsoft Excel

.tif, .lsm - Fiji (https://imagej.net/Fiji.html#Downloads)

.pzfx - GraphPad Prism

.svg - Inkscape (https://inkscape.org/)
Keywords: Biochemistry and cell biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi